Cartas a psicanalistas persistentes - Hampariam, Carol Godoi (2023)
The current essay aims at looking into the motivations which keep someone acting as a psychoanalyst, even after being aware of the difficulties and challenges of such profession. That is because the psychoanalysing does not rely on only the amount of books read, the frequency of self-analysis and the conferences or study groups which the therapist has taken part, but also on the continuous exercise of listening to the ties of the unconscious, and on learning from the transferencial traps. And why would one keep oneself acting in such demanding and unique profession? For this purpose, a qualitative research was carried out, in the form of semi-structured interviews, with 10 psychoanalysts who have been working for approximately 10 years or so with clinical practice. In order to address these interviews, the thematic analysis was used and the outcome, along with the theoretical elements which were the basis for such research, were introduced as letters addressed to psychoanalysts. We observed that the passion for psychoanalysis is one of the motivations contained in the maintenance of such profession. In this passion, there is a delight by the diversity of narratives which the analyst listens, an idealization of psychoanalysis – as in any tender affections – and also a possibility for being in love with the pshychoanalysing. Such possibility, as was also observed, is linked to an understanding of the boundaries of Psychoanalysis itself, which certain loneliness could be included. That is to say, there is a common bond, yet it remains unique every time, among the dimensions of love, passion and loneliness. Another aspect which was observed refers to the seasoned psychoanalysis’s capability to tolerate the anxiety of not being aware and, at the same time, enjoying the pleasant feeling of finding out and understanding what, beforehand, has not known or understood, which enables the professional to reinvent an innovative way of dealing with the impossibilities of psychoanalysis. Thus, we understand that the seasoned psychoanalyst keep on facing their “not idealizations”, their obstacles, their outcomes and vulnerabilities, enabling the professional to create a self-dialogue with the psychoanalysis. Therefore, they hold the position of the psychoanalyser active who introduces a (dis)position in (re)invent references which base the professional’s persistence, perseverance and emphasis in the selfanalytical work and in the others